The price of money, 1946 to 1969 : an analytical study of United States and foreign interest rates - Homer, Sidney; Johannesen, Richard I. (New Brunswick, N.J. : Rutgers University Press, 1969)
The book is a summation on bond prices, trends, relative values, yields, yield spreads and yield curves.
ucj 17/01/2019
Loans
Keywords: Interest rates; Bonds